Usability and Acceptance Analysis of Wearable BCI Devices - Ilaria Lombardi; Mario Buono; Giovanna Giugliano; Vincenzo Paolo Senese; Sonia Capece (Applied Sciences)
In the current scientific and technological scenario, wearable neuroimaging devices represent a revolution in neuroscience and wearable technology. These tools combine the features of neuroimaging technologies with the convenience of wearable devices, enabling real-time exploration of brain activity in real-world contexts. This convergence defines new perspectives in scientific research, medical diagnosis, and human performance analysis. Technologies such as EEG and fNIRS enable the non-invasive monitoring of brain activity without the need for heavy clinical equipment. Indeed, miniaturization, portability, wireless communication, and energy efficiency are key objectives in the design of advanced devices. In such a scenario, comfort is a key requirement to enable widespread use in different contexts, requiring the design of lightweight and minimally invasive wearable devices. The literature review examines the impact of wearable EEG and fNIRS devices on the user in real-life and laboratory environments in terms of usability and acceptability. The study presents evaluation and design factors—applied to laboratory testing—defined to improve the quality and perception of the user experience and to ensure the accuracy of cognitive load detection. These results will be useful in defining wearable devices, new applications, and future challenges for BCI.